Pengaruh Kinerja Keuangan, Intensitas Aset Tetap, Dan Ukuran Perusahaan Terhadap Agresivitas Pajak - Islakhun Nisak, Islakhun; Luh Nadi (AKUNTANSI 45, 2024)
This study aims to empirically determine the influence of financial performance, fixed asset intensity, and company size on tax aggressiveness in the consumer non-cyclicals manufacturing sector listed on the Indonesia Stock Exchange from 2018 to 2022. The sample selection used purposive sampling, resulting in 21 consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2018-2022 period. The data analysis employed multiple regression analysis with data processing using Eviews 12SV software. The results show that financial performance has a significant partial influence on tax aggressiveness, while fixed asset intensity and company size do not have a significant influence. However, when considered together, financial performance, fixed asset intensity, and company size collectively influence tax aggressiveness.